Structural strengthening using natural fibers composite - a review - Norliana, Bakar; Choo, Chin Siew; Siregar, J. P. (Universiti Malaysia Pahang, 2019)
In recent year research on natural fiber composites increased owing to their light weight, easy availability and improved mechanical characteristics. The natural fiber is also an environmentally friendly material, which produce less pollutant during its production. This paper presents a comprehensive review on the efficient and sustainable use of natural fiber composites in structural strengthening. In addition, detailed information on the physical and mechanical properties of natural fibers is also presented. The state-of-art technology to produce a high strength natural fiber composites are also reviewed. Comparison are also made with a conventional material such as a carbon fiber reinforced composite and a recommendation for best practices is outlined. Finally, recommendation for potential external strengthening material is presented based on the performance of the natural fiber composites.